Розвиток України у контексті загальносвітових підходів до вирішення проблеми глобального потепління - Іличок, Б. І. (Видавництво Львівської політехніки, 2015)
Дослідження розглядає проблему глобального потепління, спричиненого зростанням концентрації в атмосфері парникових газів. Вирішення цієї проблеми як в Україні, так і в глобальному масштабі, полягає у зменшенні викидів та збільшенні поглиначів парникових газів. Через зменшення вирубки і додаткове насадження лісів можна частково в природний спосіб знизити антропогенний тиск на клімат планети. Зменшення викидів парникових газів за рахунок впровадження екологічно чистих технологій, підвищення ефективності використання енергоресурсів, а також застосування альтернативних (поновлюваних) джерел енергії спроможне істотно вплинути на тенденцію зміни клімату. Досліджено питання про стан виконання Україною її зобов’язань за Рамковою Конвенцією ООН про зміну клімату щодо зменшення викидів в атмосферу парникових газів, зокрема діоксиду вуглецю. Запропоновано збільшити в Україні обсяги інвестування програм щодо зменшення антропогенного впливу парникових газів на клімат за рахунок збільшення вдвічі сьогодні чинних ставок податку за викиди в атмосферне повітря парникових газів. The study deals with the problem of global warming caused by rising concentrations of greenhouse gases in the atmosphere. Vyschenavenoyi way to solve problems in Ukraine and globally is to reduce emissions and increase sinks of greenhouse gases. A further reduction of deforestation and reforestation may be partly a natural way to reduce human pressure on the planet’s climate. Reducing greenhouse gas emissions through the introduction of environmentally friendly technologies, increase energy efficiency and use of alternative (renewable) energy sources able to significantly affect the trend of climate change. These issues are already more than 20 years is a subject of study in the implementation of UN Framework Convention on Climate Change. The question on implementation by Ukraine of its commitments under the United Nations Framework Convention on Climate Change to reduce emissions of greenhouse gases, particularly carbon dioxide. In order to reduce greenhouse gas emissions in Ukraine adopted several state programs, including the National Action Plan on Renewable Energy in 2020, the updated Energy Strategy of Ukraine till 2030. To encourage the development of renewable energy, renewable energy and alternative fuels in Ukraine in the Tax and Customs Code introduced provisions that provided significant incentives for energy companies that produce energy from renewable sources. Ukraine proposed to increase investment in programs to reduce anthropogenic greenhouse gas climate impact by doubling the existing tax rates for air emissions of greenhouse gases. Increased use of renewable energy sources in the energy balance of Ukraine also will help increase diversity of energy sources and contribute to the energy independence.
Development of Ukraine in the context of global approach to solving global warming
Keywords: парникові гази; діоксид вуглецю; глобальне потепління; Кіотський протокол; відновлювальна енергетика; екологічно чисті технології; поглиначі парникових газів; greenhouse gases; carbon dioxide; global warming; the Kyoto Protocol; renewable energy; clean technologies; sinks of greenhouse gases